Adsorption of acid yellow dye 17 on activated carbon prepared from Euterpe oleracea: kinetic and thermodynamic studies (Research, Society and Development, 2022)
Environmental pollution has been a point of discussion in the international community and an object of investigation by research groups, which focus on the development of remediation methods. In the current study, the bunch of açaí (Euterpe oleracea) was used as a precursor for the preparation of low-cost activated carbon in order to remove the dye 17 AY 17 from the aqueous solution. The synthesis was carried out at temperatures of 500, 600 and 700 °C, for 2.0 h in a muffle furnace. The kinetic and thermodynamic mechanism of the adsorption process of the acid yellow dye 17, and the effects of pH, contact time and initial concentration were investigated. Activated carbon carbonized at 700 °C had the highest adsorption capacity, about of 99.9% of removal of the AY. The adsorption capacity of AY 17 was slightly pH dependent with a maximum value at pH 2.0. The kinetic data show that the equilibrium time was 200 min, and the adsorption capacity of activated carbon was 99.9% at 50 mg L‒1 and 67.0% at 150 mg L‒1 of adsorbate, suggesting high adsorption capacity of the material, even in the presence of high dye concentration. The adsorption process of AY 17 is described by the pseudo-second order kinetic model, and the experimental adsorption isotherms are adjusted to the Freundlich model, indicating that the adsorption of AY 17 on activated carbon occurs with the formation of multilayers. The present study shows that this low-cost material has great potential for remediation of textile effluents.